KONSEP GREEN ACCOUNTING UNTUK CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE (CSR) PERUSAHAAN DI INDONESIA - Latifah, Eny; Abdullah, Rudi (JITAA : Journal Of International Taxation, Accounting And Auditing, 2022)
The aim of this research is to determine the Green Accounting Concept for Corporate Social Responsibility Disclosure for Companies in Indonesia. The research method is qualitative with the Systematic Literature Review method. The research results are that the Green Accounting Concept for Corporate Social Responsibility Disclosure  for Companies in Indonesia includes: first, Legitimate Theory where accounting has a role as a foundation in developing the theory of social responsibility disclosure. Second, Green accounting or what is known as green accounting is a renewal of ideas in accounting which focuses on the scope of accounting not just on financial transactions, events or objects, but also on social and environmental objects, transactions or events. Third, Environmental Disclosure is disclosure of information about the environment by companies as a manifestation of social responsibility, so that it can be used as an object of observation that is useful for interested parties. Fourth, Entity Theory has the concept that companies must be separated from their owners, because they are independent bodies